The impact of digital economy on the supply chain resilience of cross-border healthcare e-commerce - Liu, Jianyu; Mao, Siyi; Lu, Lin; Jing, Yuan; Yang, Xiangjun; Xu, Hejiang; Ren, Yuelin (Frontiers in Public Health, 2025)
The healthcare industry plays a crucial role in global economic development and public health, but the healthcare cross-border e-commerce supply chain often faces numerous risks due to various disruptive events. We employ panel data from 2013 to 2022 for provincial-level regions in China to investigate the impact mechanisms of the digital economy on supply chain resilience in cross-border healthcare e-commerce. The results indicate that the digital economy significantly enhance supply chain resilience, with reduced reliance on foreign trade, increased export technology complexity, and decreased export concentration being key pathways for this improvement. The impact of the digital economy is stronger in the western regions than in central and eastern areas, and the establishment of comprehensive cross-border e-commerce pilot zones can further empower the supply chain. These findings offer valuable insights for the sustainable development of healthcare cross-border e-commerce supply chain resilience and the digital economy.